Analisis Perbandingan Metode Triple Exponential Smoothing dan Metode Winter Untuk Peramalan Tingkat Hunian Hotel Aston Denpasar - Joshua Dwi Putra Tamasoleng; Ida Bagus Ary Indra Iswara (Program Studi Teknik Informatika, Fakultas Teknik. Universitas Serambi Mekkah, 2020)
Aston Denpasar Hotel is one of the five-star hotels in Bali currently requires forecasting analysis because it has constraints in determining the number of occupancy rates in the next period. The choice of method in forecasting time series largely determines the results of forecasting, so this research is conducted to find the best method of the method to be used. The method used is Triple Exponential Smoothing one parameter from brown and Winter Multiplicative and Additive methods. Based on the analysis of the best method is the Triple Exponential Smoothing one parameter method of brown with the lowest error testing with MAPE that is equal to 23.35%. While the winter multiplicative method was 28.53% and the winter additive method was 27.38%